Acriflavine targets oncogenic STAT5 signaling in myeloid leukemia cells - Hallal, Rawan (J Cell Mol Med, 2020)
Acriflavine (ACF) is an antiseptic with anticancer properties, blocking the growth of solid and haematopoietic tumour cells. Moreover, this compound has been also shown to overcome the resistance of cancer cells to chemotherapeutic agents. ACF has been shown to target hypoxia‐inducible factors (HIFs) activity, which are key effectors of hypoxia‐mediated chemoresistance. In this study, we showed that ACF inhibits the growth and survival of chronic myeloid leukaemia (CML) and acute myeloid leukaemia (AML) cell lines in normoxic conditions. We further demonstrated that ACF down‐regulates STAT5 expression in CML and AML cells but activates STAT3 in CML cells in a HIF‐independent manner. In addition, we demonstrated that ACF suppresses the resistance of CML cells to tyrosine kinase inhibitors, such as imatinib. Our data suggest that the dual effect of ACF might be exploited to eradicate de novo or acquired resistance of myeloid leukaemia cells to chemotherapy.